KOMPETENSI KOMUNIKASI ANTARBUDAYA PADA MAHASISWA ASING DI UIN SUMATERA UTARA: (STUDI PADA MAHASISWA UNIVERSITAS ISLAM NEGERI SUMATERA UTARA MEDAN) - Prisayuna, Alfathin (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
In the era of globalization, multicultural developments increasingly exist, communication being a very important study in society, the importance of communication is visible from the growing development of communication technology which is currently not foreign again with Intercultural which is the basis of communication. The communication used by foreign students is intercultural communication. In the research, the informants were foreign students from Malaysia. The purpose of this study is to look at the competencies or abilities that Malaysian students have in communicating and adapting to culture in the city of Medan. This research was conducted at the Islamic University State of North Sumatra (UIN SU). The research analysis used is qualitative approach, using the theory of anxiety/uncertainty Management (AUM), while research informants are determined linearly snowball sampling. Primary data obtained through in-depth interviews with informants. While secondary data obtained from data collection through documents in the form of books, journals, internet, and related photos with research topics. This research shows that cultural differences especially language will be a challenge for Malaysian students in communicating and adapting so that communication competence is going to be in trouble. But with the passage of time, interaction and the adaptation of Malaysian students is gradually improving and they canunderstand and understand the environment and culture in the city of Medan.